2009
DOI: 10.1152/physiolgenomics.90370.2008
|View full text |Cite
|
Sign up to set email alerts
|

Muscle genome-wide expression profiling during disease evolution in mdx mice

Abstract: Mdx mice show a milder phenotype than Duchenne patients despite bearing an analogous genetic defect. Our aim was to sort out genes, differentially expressed during the evolution of skeletal muscle mdx mouse disease, to elucidate the mechanisms by which these animals overcome the lack of dystrophin. Genome-wide microarray-based gene expression analysis was carried out at 3 wk and 1.5 and 3 mo of life. Candidate genes were selected by comparing: 1) mdx vs. controls at each point in time, and 2) mdx mice and 3) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 67 publications
6
49
0
Order By: Relevance
“…This could indicate an apparent response mechanism to reinforce the links between the ECM and the cytoskeleton, protecting the muscular fibers against contraction damages. 20 A higher expression of Gpnmb (osteoactivin) in dystrophic mice 35 and DMD patients 36 was previously described. Osteoactivin is implicated in the differentiation and function of many cell types.…”
Section: Characterization Of the Dystrophic Processmentioning
confidence: 89%
See 2 more Smart Citations
“…This could indicate an apparent response mechanism to reinforce the links between the ECM and the cytoskeleton, protecting the muscular fibers against contraction damages. 20 A higher expression of Gpnmb (osteoactivin) in dystrophic mice 35 and DMD patients 36 was previously described. Osteoactivin is implicated in the differentiation and function of many cell types.…”
Section: Characterization Of the Dystrophic Processmentioning
confidence: 89%
“…Several transcriptome studies in Dmd mdx mouse were published in the last years, [12][13][14][15][16][17][18][19][20] but no studies in Large myd − / − nor in Dmd mdx /Large myd − / − were performed. 9 In Dmd mdx , similar data to the observed in our study were described by Boer et al 14 and Porter et al 17,21 Using an Affymetrix chip of about 12 000 genes/EST, Boer et al 14 identified 58 DEGs in Dmd mdx limb muscles, from which 49 were unregulated while only 9 were downregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies led us to examine proteases that are both induced in dystrophic skeletal muscle and amenable to pharmacologic inhibition, which might represent a new therapeutic approach in DMD. One of these proteases, Ctss, was previously identified as an mRNA species up-regulated in both muscle from DMD patients and mdx mice, although the functional effects of this increase were not investigated (17)(18)(19).…”
mentioning
confidence: 99%
“…It contains four fasciclin domains that are also observed in the insect protein fasciclin I, which is involved in neuronal cell-cell adhesion (11,12). Periostin expression is low at baseline in many adult tissues, but is strongly induced and secreted into the ECM after acute injury, as well as in dystrophic skeletal muscle (13). Periostin is expressed exclusively by fibroblasts or cells that adopt a fibroblast-like phenotype after an injurious event (14).…”
mentioning
confidence: 99%